OBSTETRIC RISK. CRITICAL MOMENTS OF THE PERINATAL PROGNOSIS SYSTEM - Елена Германовна Ершова; Ольга Васильевна Ремнева (The Publishing House Medicine and Enlightenment, 2018)
In this literature review based on the study of factors influencing the level of perinatal morbidity and mortality, the concept of perinatal risk is presented, approaches to the allocation of obstetric risk groups and forecasting of perinatal outcomes are introduced, the scales of perinatal risk scoring are analyzed. There are described medical and organizational measures, including the regionalization of the obstetrics service, various options for rational choice of the term and method of delivery for the prevention of adverse perinatal outcomes.